Leveraging Green Thinking as a Motivator to Influence Consumer Purchasing Intention - Weerasekara, D. (NSBM Green University, 2022)
Over the past few years, ‘going green’ as a concept has garnered significant attention from both an academic and practical perspective. However, whilst a plethora of research has been conducted in line with the ‘green’ concept a significant knowledge gap continues to persist in the paradigm of what influences green thinking in consumers’ minds. Therefore, this paper primarily intends to utilize insights from self-determination theory to assess the relationship between green thinking and green intrinsic and extrinsic motivation. This research further contributes to the existing literature by critically evaluating the concept of ‘going green’ and ‘green purchasing intention’ from both an academic and practical perspective